2011
DOI: 10.1063/1.3531566
|View full text |Cite
|
Sign up to set email alerts
|

Inner surface enhanced femtosecond second harmonic generation in thin ZnO crystal tubes

Abstract: At room temperature, efficient second harmonic generation ͑SHG͒ emission is observed in thin ZnO crystal hollow rods ͑tubes͒ with diameter ϳ0.2 mm under the excitation of femtosecond laser from 700 to 860 nm. Power and polarization dependence of the SHG signal on the primary excitation beam is also measured. The multiple total reflections between the outer and inner surfaces of the sample are analyzed to be responsible for the efficient SHG. Ninefold amplification of SHG signal in the tube structure is estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…The polarization dependence of SHG shows a periodic variation (periodicity π for P-in/P-out and π/2 for S-in/P-out) with changes in the degree of polarization of the incident beam. The incident laser power dependence on the SHG intensity increases with the increase in incident laser power and shows very good linearity with power dependence factor of $1.91 AE 0.02, very close to the reported value (2.02 AE 0.10) for the bulk ZnO crystal [18]. Therefore, the SHG output closely follows the ideal square law dependence on the incident laser power.…”
Section: Second Harmonic Generation In Zno Nanowiressupporting
confidence: 85%
See 1 more Smart Citation
“…The polarization dependence of SHG shows a periodic variation (periodicity π for P-in/P-out and π/2 for S-in/P-out) with changes in the degree of polarization of the incident beam. The incident laser power dependence on the SHG intensity increases with the increase in incident laser power and shows very good linearity with power dependence factor of $1.91 AE 0.02, very close to the reported value (2.02 AE 0.10) for the bulk ZnO crystal [18]. Therefore, the SHG output closely follows the ideal square law dependence on the incident laser power.…”
Section: Second Harmonic Generation In Zno Nanowiressupporting
confidence: 85%
“…Studying SHG in ZnO NWs started few years ago and lot of information/knowledge has been gathered over the years by the nanoscale research community. Previous studies reported efficient generation of SHG signal from various types of ZnO nanostructures, including NWs [11][12][13][14][15][16][17][18][19][20]. Therefore, with improvement in the fabrication technique for large area ZnO NWs, it can be widely used as one of the best SHG materials.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al found that the photoluminescence energy ( E PL ) of ZnO nanocrystals increases from 3.30 to 3.43 eV and the photoabsorption energy ( E PA ) increases from 3.43 to 3.65 eV as the size decreases from 12 to 3.5 nm. Similar trends of size-dependent optical properties have also been reported for ZnO nanodots, ,, nanorods, , and nanobelts . Yuan et al found two possible mechanisms for the surface texture-induced surface tension and charge-transferring dynamics that dictate the catalytic performance of ZnO nanostructures.…”
Section: Introductionsupporting
confidence: 57%
“…On a different scale, efficient SHG was experimentally observed from bigger structures, namely hollow ZnO rods having diameters of 200 m and length of a few millimiters [85]. A fs laser tuned at 774 nm was employed to excite SHG.…”
Section: Shg In Zno Nanostructuresmentioning
confidence: 99%